Marker assisted backcrossing of alcobaca gene into two elite tomato breeding lines - Kwabena Osei, Michael; Danquah, Agyemang; Adu-Dapaah, Hans; Danquah, Eric; Blay, Essi; Massoudi, Mark; Maxwell, Douglas (Frontiers in Horticulture, 2022)
Tomato is one of the most important vegetable crops cultivated and consumed worldwide. Demand is increasing daily because of increase in per capita fresh fruit consumption. Despite the economic importance of tomato, it has relatively short shelf-life after ripening and experiences remarkable post-harvest losses. This study was aimed at using marker-assisted backcrossing (MABC) to transfer shelf-life gene (alc) into the genetic background of two elite Ghanaian tomato breeding lines. The MABC derived lines at BC2F3 were evaluated to confirm selections using molecular markers. All the MABC-derived lines gave significant extended shelf life compared to the checks except for Alc-LA3134, the alc donor parent, which was, however, not significantly different from one of the backcrosses (BC2F2.3-E-80-19-26). This confirms that the genetic regulation of the shelf-life trait is dependent on the alc gene. The performance of the donor check (Alc-LA3134) against the 12 MABC-derived lines indicated no significant differences for the fruit firmness (except for BC2F2.3-E-80-19-4), number of locules per fruit and shelf life (for only BC2F2.3-E-80-19-26), thus suggesting similar backgrounds of the MABC as the recurrent parents. A considerable increase in the shelf-life value was observed among the MABC-derived lines. The introgression of the alc gene into cultivated tomatoes for extended shelf-life could reduce post-harvest losses of tomato in Ghana.